Prerequisites for the Creation of the Ukrainian Autocephalous Orthodox Church (1989-1990) - Khomitsky, Vasyl (Journal of Education, Health and Sport, 2024)
The article analyzes the socio-political and religious processes in Ukraine in the late 1980s that led to the establishment of the Ukrainian Autocephalous Orthodox Church. The catalyst for these events was the period of Gorbachev's perestroika, the processes of liberalization and democratization that emerged on the background of the systemic crisis of the Soviet Union. It is established that the key event was the 1988 anniversary celebration of the baptism of the Kyivan Rus'. The Russian Orthodox Church decided to change the Statute of the Church, according to which the abbot of the church became the head of a religious organization, and the Church became a legal organization. This significantly reorganized the religious life of the community. The events that led to the First Synod of the UAOC in June 1990 are traced. The Ukrainian clergy went through a difficult path in the process of recovery of the Ukrainian Orthodox Church. The author outlines the main problems of the transition period for believers: visitors to churches may not have known to which church jurisdiction they belonged, long-lasting misunderstandings and persecution between representatives of different churches, and the activities of the ROC clergy were threatening to the Ukrainian nation. It is found that the election of Metropolitan Mstyslav (Skrypnyk), who was a nephew of Simon Petliura, as Patriarch of the UAOC inspired the Ukrainian people to believe in changes in the organization of the Church. However, in the process of institutionalizing the UAOC, misunderstandings between Patriarch Mstyslav and Metropolitan Ivan (Bodnarchuk) divided the believers and clergy. Research methods. In the course of the research, the methods of induction and deduction, analysis and synthesis, сomparative historical research, and systemic historical research were used. The principles of objectivity, non-denominationality, tolerance, and priority of documents were applied. The conclusions emphasize that the revival of the UAOC was based on the interaction of nationally oriented socio-political forces and the clergy. The processes of democratization of society accelerated the development of the autocephalous movement, which aimed to declare independence from the Moscow Patriarchate of the Ukrainian Orthodox Church. This initiative received the greatest support among the clergy and believers in the western regions of Ukraine. Protoiereus Volodymyr (Yarema), Bishop Ivan (Bodnarchuk), and Metropolitan Mstyslav (Skrypnyk) played a special role in the events of the UAOC creation.